Sleep stage classiﬁcation based on multi-level feature learning and recurrent neural networks via wearable device - Zhang, Xin; Kou, Weixuan; Chang, Eric; Gao, He; Fan, Yubo; Xu, Yan (Computers in Biology and Medicine, 2018)
Background: Automatic sleep stage classiﬁcation is essential for long-term sleep monitoring. Wearable devices show more advantages than polysomnography for home use. In this paper, we propose a novel method for sleep staging using heart rate and wrist actigraphy derived from a wearable device. Methods: The proposed method consists of two phases: multi-level feature learning and recurrent neural networks-based (RNNs) classiﬁcation. The feature learning phase is designed to extract low- and mid-level features. Low-level features are extracted from raw signals, capturing temporal and frequency domain properties. Midlevel features are explored based on low-level ones to learn compositions and structural information of signals. Sleep staging is a sequential problem with long-term dependencies. RNNs with bidirectional long short-term memory architectures are employed to learn temporally sequential patterns. Results: To better simulate the use of wearable devices in the daily scene, experiments were conducted with a resting group in which sleep was recorded in the resting state, and a comprehensive group in which both resting sleep and non-resting sleep were included. The proposed algorithm classiﬁed ﬁve sleep stages (wake, non-rapid eye movement 1–3, and rapid eye movement) and achieved weighted precision, recall, and F1 score of 66.6%, 67.7%, and 64.0% in the resting group and 64.5%, 65.0%, and 60.5% in the comprehensive group using leaveone-out cross-validation. Various comparison experiments demonstrated the eﬀectiveness of the algorithm. Conclusions: Our method is eﬃcient and eﬀective in scoring sleep stages. It is suitable to be applied to wearable devices for monitoring sleep at home.